2019
DOI: 10.1177/1747021819829696
|View full text |Cite
|
Sign up to set email alerts
|

EPS mid-career prize lecture 2017: Writing systems, reading, and language

Abstract: Skilled reading reflects an accumulation of experience with written language. Written language is typically viewed as an expression of spoken language, and this perspective has motivated approaches to understanding reading and reading acquisition. However, in this article, I develop the proposal that written language has diverged from spoken language in important ways that maximise the transmission of meaningful information, and that this divergence has been central to the development of rapid, skilled reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 102 publications
0
16
0
1
Order By: Relevance
“…Although these two theoretical descriptions of the production process involved in oral language and writing make it clear that they are not identical (Rastle, 2019), both communication modes rely on many of the same underlying knowledge resources (e.g., phonological, morphological, semantic, syntactic, and pragmatic knowledge) and apply similar production processes (e.g., generating and monitoring intentions and production, translating messages/ideas into acceptable language, bringing this language to life by articulating it or putting it into written form). Theoretically then, difficulties with oral language skills or processes may manifest themselves in children's writing, as both oral language and writing draw on the same or similar knowledge and processes (Connelly et al, 2012).…”
Section: Shared Knowledge Theorymentioning
confidence: 99%
“…Although these two theoretical descriptions of the production process involved in oral language and writing make it clear that they are not identical (Rastle, 2019), both communication modes rely on many of the same underlying knowledge resources (e.g., phonological, morphological, semantic, syntactic, and pragmatic knowledge) and apply similar production processes (e.g., generating and monitoring intentions and production, translating messages/ideas into acceptable language, bringing this language to life by articulating it or putting it into written form). Theoretically then, difficulties with oral language skills or processes may manifest themselves in children's writing, as both oral language and writing draw on the same or similar knowledge and processes (Connelly et al, 2012).…”
Section: Shared Knowledge Theorymentioning
confidence: 99%
“…Based on analysis of performance on a large-scale lexical decision task, Brysbaert, Stevens, Mandera and Keuleers (2016) estimated that the average 20-year-old speaker of American English knows around 71,400 words. However, this count includes overlapping words: knowing the word accept goes a long way to supporting understanding of unacceptable (Rastle, 2019). When inflections of a given word are ignored (e.g., accepts, accepting and accepted all listed under accept), estimates of vocabulary size drop to 42,000 unique lemma types, and they are further reduced if morphological families are combined under their base word (e.g., acceptable and unacceptable counted as accept), leaving an estimated vocabulary size of only 11,100 unique base words (Brysbaert et al, 2016).…”
Section: Highlightsmentioning
confidence: 99%
“…Once children can read, they have the opportunity to learn new words via reading (Nagy, Anderson & Herman, 1987) and to absorb the rich morphological cues to meaning that are evident in spelling patterns (Rastle, , 2019. Reading also provides experience with syntactic structures that are quite rare in conversation (Montag & McDonald, 2013).…”
Section: Nation/simple View 31mentioning
confidence: 99%
“…Numerous studies have found associations between children's reading comprehension and their knowledge and appreciation of morphology (e.g., Levesque, Kieffer & Deacon, 2019;Tong, Deacon, Kirby, Cain & Parrila, 2011), consistent with morphology being a critical component of linguistic comprehension. At the same time, however, skilled word recognition is highly sensitive to morphological regularities that are marked in the orthography, reminding us that English is a morphophonemic in nature (Rastle, 2019;Venezky, 1999). As reading develops, the word recognition system comes to embody this structure and this is reflected in how single words are read and processed (e.g., Kearns & Al Ghanem, in press;Dawson, Rastle & Ricketts, 2017).…”
Section: Part Iv: Reflections On the Simple Viewmentioning
confidence: 99%